Following the flow—Microbial ecology in surface‐ and groundwaters in the glacial forefield of a rapidly retreating glacier in Iceland. (13th July 2022) - Purkamo, Lotta; Ó Dochartaigh, Brighid; MacDonald, Alan; Cousins, Claire
Abstract: The retreat of glaciers in response to climate change has major impacts on the hydrology and ecosystems of glacier forefield catchments. Microbes are key players in ecosystem functionality, supporting the supply of ecosystem services that glacier systems provide. The interaction between surface and groundwaters in glacier forefields has only recently gained much attention, and how these interactions influence the microbiology is still unclear. Here, we identify the microbial communities in groundwater from shallow (<15 m deep) boreholes in a glacial forefield floodplain ('sandur') aquifer at different distances from the rapidly retreating Virkisjökull glacier, Iceland, and with varying hydraulic connectivity with the glacial meltwater river that flows over the sandur. Groundwater communities are shown to differ from those in nearby glacial and non‐glacial surface water communities. Groundwater–meltwater interactions and groundwater flow dynamics affect the microbial community structure, leading to different microbial communities at different sampling points in the glacier forefield. Groundwater communities differ from those in nearby glacial and non‐glacial surface waters. Functional potential for microbial nitrogen and methane cycling was detected, although the functional gene copy numbers of specific groups were low.